Penilaian Legalitas Perdagangan Kripto di Pasar Komoditas Indonesia: Studi Analitis Berbasis MaqÄá¹£id Al-SharÄ«Ê¿ah. - Bakhrul Huda; Rianto Anugerah Wicaksono; Mochammad Andre Agustianto; Fadllan Fadllan (Universitas Islam Negeri Antasari Banjarmasin, 2025)
Cryptocurrency trading has emerged as a global phenomenon, raising complex legal and ethical questions, particularly within the framework of Islamic law. In Indonesia, the government’s dual-track policy—legalizing crypto assets as commodities while prohibiting them as payment instruments—calls for critical normative analysis. This study aims to assess the legality of cryptocurrency trading in Indonesia’s futures market from the perspective of maqāṣid al-sharīʿah. Employing a normative legal research method integrated with a maqāṣid-based approach, the research analyzes statutory regulations and incorporates primary data from interviews with regulatory authorities (BAPPEBTI). The findings reveal that the legalization policy aligns with aspects of public interest (maṣlaḥah) and falls within the categories of maqāṣid ḥājiyyah and maʿānin ʿurfiyyah ʿāmmah, although continuous monitoring is essential to prevent elements of maysir, gharar, and ḍarar. The uniqueness of this research lies in its synthesis of legal formalism with maqāṣidic reasoning, supported by empirical insights, offering a novel contribution to the field of Islamic economic law. Future research should include comparative studies across Muslim jurisdictions to develop a sharīʿah-compliant regulatory framework responsive to fintech innovation.